(untitled) (Journal of Tourism and Himalayan Adventures, 2020)
The climate change in the Nepal-Himalayan region is not just about increased temperature and subsequent glacier melting. It speaks to broad questions on the relationship between society and the environment, science and knowledge, global and local. The present study analysis supports the understanding and responses of agropastoral communities on climate change in Nhāson valley of the southeast Manang District. The stories from local participants were documented and analyzed for their agro-pastoral experience. The communities inhabit in the place engaging in daily activities and accommodate practices to cope with anthropogenic climate change. The paper is based on nine months ethnographic study (from 2012-2018) undertaken in six settlements that practice agro-pastoralism for livelihood. In addition, quantitative data was also used to supplement local narratives about the changes in environmental phenomena visually in the local real world. The findings depict that the mountain agro-pastoral communities are more aware with the environmental changes associated with climatic variables. The communities’ observation is grounded on the lived experience. Moreover, climate surpasses many disciplinary boundaries. Both, qualitative information based on local narratives and quantitative data, offer complementary to address complexities of global climate change.